Politeness in Classroom Directives: A Pragmatic Analysis of Indonesian Language Teachers’ Speech Acts in Kikim Selatan Junior High Schools - Noprilia Noprilia; Tressyalina Tressyalina (STAI Hubbulwathan Duri, 2025)
Effective teacher-student communication is essential in educational settings, particularly through directive speech acts guided by politeness principles. This study investigates how Indonesian language teachers in junior high schools in Kikim Selatan District utilize directive speech acts and politeness strategies during classroom instruction. A qualitative descriptive approach was employed, involving five teachers from four different schools. Data were collected through non-participant classroom observations and audio recordings. The analysis followed the Miles and Huberman interactive model, focusing on categorizing types of directive speech acts and identifying politeness principles. The analysis revealed a predominance of commands (70 instances) and challenges (49), with advising (23), suggesting (15), and requesting (5) used less frequently. The most commonly applied politeness principles were generosity (41 instances) and appreciation (38), which served to reduce the potential for face-threatening acts and foster a more respectful classroom environment. The choice of speech acts was context-dependent: calm classroom settings facilitated clear instructions and challenges, while noisy environments prompted more assertive and persuasive strategies. These findings highlight the nuanced application of speech acts influenced by classroom dynamics and underscore the importance of integrating politeness strategies into instructional communication. Teachers adapted their language based on environmental cues to maintain engagement and authority while preserving student rapport. The study contributes to the broader understanding of educational discourse by demonstrating the role of politeness in directive communication. It suggests practical applications for teacher training programs to enhance communication flexibility and empathy in classroom management.